PENGARUH KEPEMIMPINAN ALTURISTIK LURAH TERHADAP PELAYANAN PUBLIK MELALUI INOVASI DI KECAMATAN TEMBILAHAN HULU - Belino, Mela Lividia; Abdillah, Muhammad Rasyid; Wardi, Jeni (Komunitas Manajemen Kompetitif, 2026)
This research examines how altruistic leadership by village heads impacts public services via innovation in Tembilahan Hulu District. Effective public services play a crucial role in local growth, yet they frequently encounter hurdles like scarce human resources, intricate administrative processes, and insufficient creativity. Altruistic leadership, which prioritizes community needs, is anticipated to spark innovative practices that elevate service standards. To identify variable interdependencies, the study uses a quantitative approach with a causal framework. It draws from 150 community members who use the services, selected through a full census. Information was gathered using surveys assessing views on altruistic leadership, innovation levels, and service excellence, then analysis using PLS-SEM (Partial Least Squares Structural Equation Modeling) to confirm hypotheses. Findings reveal that altruistic leadership positively and significantly affects both innovation and public services, but innovation lacks a notable direct influence on services and fails to bridge the two. The work offers theoretical and applied insights into refining local leadership frameworks, along with suggestions for bolstering community-driven innovation to better public services.